Determination of subsurface lineaments in the Hoang Sa islands using enhanced methods of gravity total horizontal gradient - Pham Thanh, Luan; Oksum, Erdinc; Kafadar, Ozkan; Phan Trong, Trinh; Nguyen Viet, Dat; Vo Thanh, Quynh; Le Thi, Sang (Vietnam Journal of Earth Sciences, 2022)
The Hoang Sa islands, located in the northern part of the East Vietnam Sea, lack information on geological structural boundaries. The gravity data from the global marine gravity model were analyzed using the enhanced total horizontal gradient methods to delineate geological structures that appear as lineaments on the transformed gravity anomaly maps of the area. Before applying the techniques to gravity data of the Hoang Sa islands, their effectiveness was demonstrated by comparing them with the results from the total horizontal gradient method for a synthetic model. Applying the enhanced horizontal gradient methods shows that most of the lineaments identified in the Hoang Sa islands are trending in the WSW-ENE, NE-SW, E-W, WNW-ESE and NNW-SSE directions. These results provide a better understanding of the subsurface structural features of the islands.